(untitled) - Cushner, Kenneth (New York, 2009)
This book is a research-based, comprehensive text designed to provide an introduction to multicultural education and diversity in society. It provides an updated and broad treatment of the various forms of human diversity found in todays schools including nationality, ethnicity, race, religion, gender, class, language, sexual orientation, and ability levels.
Keywords: Multicultural education,Individual differences in children,Sex differences in education,Giáo dục đa văn hóa,Sự khác biệt ở mỗi cá thể trẻ em,Khác biệt về giới tính trong giảng dạy; United State,United State,United State,Hoa Kỳ,Hoa Kì,Hoa Kì